2014
DOI: 10.1051/0004-6361/201424055
|View full text |Cite
|
Sign up to set email alerts
|

The H i hole and AGB stellar population of the Sagittarius dwarf irregular galaxy

Abstract: Using two HST/ACS data sets that are separated by about two years has allowed us to derive the relative proper motion for the Sagittarius dwarf irregular (SagDIG) and reduce the heavy foreground Galactic contamination. The proper-motion decontaminated SagDIG catalog provides a much clearer view of the young red-supergiant and intermediate-age asymptotic giant branch populations. Previously identified carbon-and oxygen-rich star samples, which are based on narrow-band filter photometry, were complemented by mem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 52 publications
(102 reference statements)
0
14
0
Order By: Relevance
“…The explosion would not have affected the positions of the stars, which fill the hole. However, Momany et al (2014) found that even young stars can be found in the hole, which could indicate that the hole was formed by gravitational instability rather than stellar feedback. On the other hand, a study of similar kiloparsec-sized H I holes in five nearby dIrrs found that the underlying stellar population produced sufficient energy to create the holes (Warren et al 2011).…”
Section: Comparison Of the Stellar And Gas Kinematicsmentioning
confidence: 99%
“…The explosion would not have affected the positions of the stars, which fill the hole. However, Momany et al (2014) found that even young stars can be found in the hole, which could indicate that the hole was formed by gravitational instability rather than stellar feedback. On the other hand, a study of similar kiloparsec-sized H I holes in five nearby dIrrs found that the underlying stellar population produced sufficient energy to create the holes (Warren et al 2011).…”
Section: Comparison Of the Stellar And Gas Kinematicsmentioning
confidence: 99%
“…Both of these characteristics point to an AGB nature. Three additional confirmed O-rich stars in Sag DIG that were identified by Momany et al (2014) are included in our near-IR HST coverage. These three stars have very red F606W-F814W colors, suggesting substantial circumstellar dust, but we do not detect dust around these stars.…”
Section: Dusty M Starsmentioning
confidence: 99%
“…As noted above, Gullieuszik et al (2007) find V1 to be blended. In the Momany et al (2014) catalogue, there are measurements in 3 bands for 11 stars inside a circle of diameter 3 arcsec centred on the variable. Using these data we estimate that the neighbouring stars contribute only about 0.1 mag to the J mean magnitude of the variable, and probably somewhat less to K S , so its position in the K S , J − K S (Fig.…”
Section: The M Star: V1mentioning
confidence: 99%